The Right to health : a multi-country study of law, policy and practice - Toebes, Brigit; Ferguson, Rhonda; Markovic, Milan M.; Nnamuchi, Obiajulu (T.M.C. Asser Press Imprint: T.M.C. Asser Press, 2014)
With a Foreword by Paul Hunt, University of Essex, UN Special Rapporteur on the Right to Health (2002-2008) "The key challenge confronting the health and human rights movement is the translation of international and national human rights law into operational policies, programmes and other health-related interventions. Nowhere is this more challenging - and more important - than within countries." (from the Foreword by Paul Hunt) This interdisciplinary study analyses how the internationally guaranteed human 'right to health' is realized by States at a national level. It brings together scholars from more than ten different countries, each of them analyzing the right to health in his or her country or region. They all focus on particular themes that are important in their country, such as health inequalities, the Millennium Development Goals, or the privatization of healthcare. And despite the differences in context, lessons can be learned from the rich experiences of the others, to learn how different countries implement (or not) health-related rights. In this book scholars, practitioners and policy makers in the fields of human rights law, health law, public health and their intersections will find a rich source of information, giving a boost to the international debate on propagation and implementation of the universal Right to Health.